Effect of biogas enriched with hydrogen on the operation and performance of a diesel-biogas dual engine (2013)
ABSTRACT: The effect of hydrogen enrichment was tested for a diesel-biogas dual fuel engine. The operation and performance characteristics, such as thermal efficiency, pollutant emissions and combustion parameters were determined. Experiments have been carried with a stationary compression ignition (CI) engine coupled with a generator in dual mode using a typical biogas composition of 60% vol. CH4 and 40% vol. CO2. For every load engine evaluated, the hydrogen concentration was varied from 5 to 20% H2 v/v. The results showed increases in peak pressure chamber up to 10.7 bar, and diesel substitution levels up to 80% under conditions of steady combustion without knocking. Also, thermal efficiency increases up to 16% and carbon monoxide emissions decreases up to 13% at full load, and 20% of hydrogen in engines operating in diesel-biogas dual mode.